Myocardial response to a triathlon in male athletes evaluated by Doppler tissue imaging and biochemical parameters - Leetmaa, T. H.; Dam, A.; Glintborg, D.; Markenvard, J. D. (Scandinavian Journal of Medicine & Science in Sports, 2008)
The aim of this study was to examine cardiac dysfunction following ultra-endurance exercise in male athletes. Fourteen athletes (mean±SD, age 39±8 years) were evaluated before and after the European Championship in Triathlon 2003 using echocardiogram (ECG), cardiac markers [cardiac troponin T (cTnT) and pro-brain natriuretic peptide (pro-BNP)] and echocardiography. Conventional echocardiography techniques and new Doppler tissue imaging (DTI) modalities were applied before and immediately after the competition. Blood samples were drawn 1 week before, immediately after and 12-24 h post-competition. CTnT significantly increased immediately, but decreased to within normal limits 12-24 h post-competition. Pro-BNP was significantly increased immediately post-race (27±21 vs 7±2 pmol/L pre-race, P=0.007), which 12-24 h later, decreased to 19±14 pmol/L (P=0.07 vs pre-race). During echocardiography, no significant differences were found in regional or global systolic parameters. Early diastolic peak flow velocity (9±2, P=0.04) and E/A ratio (2±1, P=0.004) were increased pre-race and decreased significantly toward normal values. In one athlete, cTnT levels increased significantly and systolic velocities decreased, thus suggesting reversible cardiac fatigue. When using cardiac markers and echocardiographic findings, a triathlon was found to have no significant negative effects on left ventricular function or myocardial tissue in male athletes.